Sources and Financial Consequences of Radical Innovation: Insights from Pharmaceuticals - Sorescu, Alina B.; Chandy, Rajesh K.; Prabhu, Jaideep C. (Journal of Marketing, 2003)
Radical innovations are engines of economic growth and the focus of much academic and practitioner interest, yet some fundamental questions remain unanswered. The authors use theoretical arguments on the risk associated with radical innovations, and the resources needed for them, to answer the following questions on the sources and financial consequences of radical innovation: (1) Who introduces a greater number of radical innovations: dominant or nondominant firms? (2) How great are the financial rewards to radical innovations, and how do these rewards vary across dominant and nondominant firms? (3) Is it only a firm's resources in the aggregate or also its focus and leverage of resources that make its innovations more financially valuable? and (4) Which are more valuable: innovations that incorporate a breakthrough technology or innovations that provide a substantial increase in customer benefits? The authors pool information from a disparate set of sources in the pharmaceutical industry to study these questions. Results indicate that a large majority of radical innovations come from a minority of firms. The financial rewards of innovation vary dramatically across firms and are tied closely to firms’ resource base. Firms that provide higher per-product levels of marketing and technology support obtain much greater financial rewards from their radical innovations than do other firms. Firms that have greater depth and breadth in their product portfolio also gain more from their radical innovations.